Zastosowanie retrospektywnego dynamicznego wskaźnika konkurencji do oceny oddziaływania drzew sąsiednich na przyrost pierśnicowego pola przekroju jodły (Abies alba Mill.) - Pach, Maciej; Soberka, Michał (Leśne Prace Badawcze, 2011)
This research was carried out in two sample plots located in silver fir plantations mixed with beech (Fagus sylvatica) and spruce (Picea abies) in the Beskid Żywiecki Mountains (Węgierska Górka Forest District, Żabnica Forest sub-district). The aim of the study was to determine the influence of neighbouring trees (namely, fir, beech, spruce) on the basal area increment of the selected fir trees depending on the size (radius) of competition zones. During the study two static competition indices (Hegyi and Ch) and a retrospective dynamic competition index (Ci) were used. Based on the cumulative value of the latest competition index, all firs were clustered into groups of constant competition dynamics over time using Euclidean distance. The analysis indicated that the grouped firs were significantly different in terms of the basal area increment over the last 10 years, in terms of crown width, coefficient of slenderness and live crown ratio. These values decreased (apart from the coefficient of slenderness) with an increase in the cumulative retrospective dynamic competition index. In both stands, an increase in the total basal area of neighbouring trees, successively growing at a distance of 2, 3, 4 and 5 metres, had a negative influence on the basal area of the selected firs. In the Żabnica II sample, there were some differences in the competition interactions between the firs and the two other species. Because of the relationships between the cumulative retrospective dynamic competition index and many features of the subject trees and the neighbouring stand, and considering the time factor, we advise that this competition index is applied in studies of inter-specific and intra-specific tree competition.